2016 IEEE International Symposium on Information Theory (ISIT) 2016
DOI: 10.1109/isit.2016.7541725
|View full text |Cite
|
Sign up to set email alerts
|

A geometric analysis of phase retrieval

Abstract: Can we recover a complex signal from its Fourier magnitudes? More generally, given a set of m measurements, y k = |a * k x| for k = 1, . . . , m, is it possible to recover x ∈ C n (i.e., length-n complex vector)? This generalized phase retrieval (GPR) problem is a fundamental task in various disciplines, and has been the subject of much recent investigation. Natural nonconvex heuristics often work remarkably well for GPR in practice, but lack clear theoretical explanations. In this paper, we take a step toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
364
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(368 citation statements)
references
References 60 publications
(80 reference statements)
4
364
0
Order By: Relevance
“…al. [36] reveal that the nonconvex objective (1.5) actually has a benign global geometry: with high probability, it has no bad critical points with m ≥ Ω(n log 3 n) samples 4 . Such a result enables initialization-free nonconvex recovery 5 [42,43].…”
Section: Comparison With Literaturementioning
confidence: 99%
“…al. [36] reveal that the nonconvex objective (1.5) actually has a benign global geometry: with high probability, it has no bad critical points with m ≥ Ω(n log 3 n) samples 4 . Such a result enables initialization-free nonconvex recovery 5 [42,43].…”
Section: Comparison With Literaturementioning
confidence: 99%
“…Despite the general intractability, recent years have seen progress on nonconvex procedures for several classes of problems, including low-rank matrix recovery [24,45,50,51,56,64,75,80,84,89,90], phase retrieval [11,13,17,25,56,61,68,74,81,86,87], dictionary learning [72,73], blind deconvolution [54,56], and empirical risk minimization [58], to name just a few. For example, we have learned that several problems of this kind provably enjoy benign geometric structure when the sample complexity is sufficiently large in the sense that all local stationary points (except for the global optimum) become saddle points and are not difficult to escape [7,34,53,72,73].…”
Section: Nonconvex Optimizationmentioning
confidence: 99%
“…For example, we have learned that several problems of this kind provably enjoy benign geometric structure when the sample complexity is sufficiently large in the sense that all local stationary points (except for the global optimum) become saddle points and are not difficult to escape [7,34,53,72,73]. For the problem of solving certain random systems of quadratic equations, this phenomenon arises as long as the number of equations or sample size exceeds the order of n log 3 n, with n denoting the number of unknowns [74]. 1 We have also learned that it is possible to minimize certain nonconvex random functionals-closely associated with the famous phase retrieval problem-even when there may be multiple local minima [13,17].…”
Section: Nonconvex Optimizationmentioning
confidence: 99%
“…Phase retrieval can be viewed as a nonconvex optimization problem [37]. In general, such optimization problems pose a challenge as they can have spurious local minimizers, saddle points, and significant sensitivity to good initialization; However, it has been shown that PR can achieve convergence using Stochastic Gradient Descent (SGD) [18].…”
Section: Analytical Gradient For Phase Retrievalmentioning
confidence: 99%